It's All About MeE: Using Structured Experiential Learning (“e”) to Cr awl the Design Space - Pritchett, Lant; Samji, Salimah; Hammer, Jeffrey (Center for Global Development, 2013)
This paper argues that within-project variations in design can serve a s their own counterfactual, reducing the incremental cost of evaluatio n and increasing the direct usefulness of evaluation to implementing a gencies. It suggests combining monitoring (‘M’), structured experienti al learning (‘e’), and evaluation (‘E’) so as to facilitate innovation and organisational capability building while also providing accountab ility …